Deep Venous Procedures Performed in the National Health Service in England between 2005 and 2015. (October 2017) - Lim, C.S.; Shalhoub, J.; Davies, A.H.
Abstract : Objectives: Recent advances in imaging technology and endovenous interventions have revolutionised the management of specific groups of patients with deep venous pathology. This study aimed to examine data published by Hospital Episode Statistics (HES) to assess trends in the number of endovascular and open surgical deep venous procedures performed in National Health Service (NHS) hospitals in England between 2005 and 2015. Materials and methods: The main diagnosis of deep venous thrombosis (DVT), and total number of primary open and percutaneous procedures for deep venous pathology for patients admitted to the NHS hospitals in England from 2005 to 2015 were retrieved from the HES database and analysed. Results: An overall declining trend in the annual number of admissions for a primary diagnosis of DVT was observed (linear regression r 2  = 0.9, p  < .0001). The number of open surgical procedures for removal of thrombus remained largely unchanged (range 26–70); the frequency of percutaneous procedures increased steadily over the study period (range 0–311). The number of open surgical procedures relating to the vena cava fell between 2005 and 2009, and remained around 50 per year thereafter. Annual numbers of cases of deep venous bypass (range 17–33) and venous valve surgery (range 8–47) remained similar in trend over this period. The number of vena cava stent (range 0–405), other venous stent (range 0–316), and percutaneous venoplasty (range 0–972) procedures increased over the first 5 years of the study period. Conclusions: There is an increasing trend in relation to endovenous procedures but not open surgery, being carried out for deep venous pathology in the last decade in NHS hospitals in England. Despite a number of limitations with HES, the increase in the number of endovenous procedures shown is likely to have significant implications for the provision of care and healthcare resources for patients with deep venous pathology.